Energetic Macroscopic Representation of a linear reciprocating compressor model. (April 2015) - Heidari, Mahbod; Wasterlain, Sébastien; Barrade, Philippe; Gallaire, François; Rufer, Alfred
Abstract: This article introduces the energetic macroscopic representation (EMR) as approach for the dynamic nonlinear modeling of a reciprocating air compressor. EMR has been introduced recently for research development in complex electromechanical systems and is based on action reaction principle. The compressor is divided into simple subsystems including: driver mechanism, cylinder head, valves and reservoir. Models are developed for different subsystems, which are assembled into a final overall system EMR. Since the final application of this model will be an isothermal Compressed Air Energy Storage system (CAES), special attention has been paid to transient heat transfer considering the thermal resistor and capacitor effect of the walls adopting a thermoelectric analogy. The results were verified both using Finite Element method and experiment. The EMR modeling presented here allows the modeling of multi-physics components and highlights the interactions of the electromechanical, heat transfer and fluid mechanics phenomena that occur simultaneously in an air compressor. Highlights: Energy flow is shown focusing on causality principle between action/reaction pair. The presented model serves as a building block for a complicated finned compressor. In thermo-pneumatic multiport, p / m ˙ regarded as pneumatic and T / E ˙ as thermal bond. Pseudo EMR is a powerful resource for modeling of convective thermodynamic systems. Effective power is subtraction of no load mode and filling mode power.